INFLUENCE OF PROJECT MANAGEMENT INFORMATION SYSTEM ON PROJECT PERFORMANCE IN COMMERCIAL BANKS IN NAIROBI, KENYA - KAMAU, JEREMIAH; Pedo, Maurice (International Journal of Entrepreneurship and Project Management, 2021)
Purpose: Therefore, the study sought to establish the influence of PMIS on credit digitization in commercial banks in Kenya. Methodology: The target population for the study was the 42 commercial banks in Kenya. The study employed a descriptive survey design and was census of the 42 commercial banks head offices in Nairobi, Kenya. Data was collected by use of a structured questionnaire. The data was cleaned, coded and analyzed using a Statistical software (SPSS). The findings were presented in form of tables, charts and graphs. Descriptive statistics were deduced from the data. From this, inferential statistics were presented and associations drawn. Regression analysis was interpreted and appropriate conclusions made. Findings: The findings from regression analysis showed that expertise of the project team, end-user involvement, project risk management and project monitoring and evaluation positively and significantly influence credit digitalization in Kenyan Commercial banks. Unique contribution to theory, practice and policy: The study was guided by the lenses of Stakeholder Management theory, Technology Acceptance Model (TAM) and the Theory of Disruptive Innovation from which the study operationalized the variables of PMIS Implementation and Credit Digitization. Banks should conduct training to all team members before commencement and during project execution. Moreover banks should involve customers in testing of projects before launching and should consider the feedback from customers